2014
DOI: 10.1038/npp.2014.63
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of MIR137 on Dorsolateral Prefrontal–Hippocampal Functional Connectivity in Healthy Subjects

Abstract: A recent mega-analysis combining genome-wide association study data revealed that a variant of microRNA 137 (MIR137) exhibits the most significant association with schizophrenia. Other biological evidence also consistently suggests that MIR137 may have a pivotal role in the pathogenesis of schizophrenia. However, the underlying neural mechanism remains unclear. As the disrupted dorsolateral prefrontal cortex (DLPFC) coupling with the hippocampal formation (HF) has been widely observed in schizophrenia patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 51 publications
(95 reference statements)
1
35
0
1
Order By: Relevance
“…The same procedure was used in our previous study (Liu et al, 2014). A total of 9108/9094 out of the 10 000 comparisons made between groups of equal sample sizes indicated that the GMV of the left/right medial temporal cortex was significantly lower in the A allele carrier subsample than those in the GG group ( Po0.05), whereas none of the comparisons showed the inverse result (two-sample t-tests, All P40.05).…”
Section: Structural Mrimentioning
confidence: 81%
See 2 more Smart Citations
“…The same procedure was used in our previous study (Liu et al, 2014). A total of 9108/9094 out of the 10 000 comparisons made between groups of equal sample sizes indicated that the GMV of the left/right medial temporal cortex was significantly lower in the A allele carrier subsample than those in the GG group ( Po0.05), whereas none of the comparisons showed the inverse result (two-sample t-tests, All P40.05).…”
Section: Structural Mrimentioning
confidence: 81%
“…Previous studies have showed the laterality effects for prefrontal effects in normal controls (Van Horn et al, 1996), and the right DLPFC showed greater recruitment during the WM task in siblings of schizophrenia compared with normal controls (MacDonald et al, 2009). The connectivity of only right DLPFC with HF was found to be disrupted in schizophrenia patients (Meyer-Lindenberg et al, 2005) and high-risk individuals (Liu et al, 2014;Rasetti et al, 2011). The effect of BIN1 genotype on brain structure and FC can be interpreted by the hypothesis that the reduction in HF-DLPFC functional connectivity leads to a compensatory increase in hippocampal volume to maintain performance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In line with that, the largest schizophrenia genome-wide association studies (GWAS) conducted to date identified variants within the hsa-miR-137 host gene, MIR137HG , as well as variants within validated miR-137 target genes to be among the top risk variants for schizophrenia [39, 40], suggesting a potential role for the miRNA in the disorder. Several studies suggest that one of the identified MIR137HG variants is associated with schizophrenia-related intermediate phenotypes such as dorsolateral prefrontal cortex hyperactivation [41] and dorsolateral prefrontal-hippocampal functional connectivity [42]. Furthermore, Wright et al [43] found significant enrichment for schizophrenia-associated genes among the list of potential and experimentally validated miR-137 targets, as well as significant enrichment of targets within schizophrenia-relevant canonical pathways, such as those involved in neuronal function and development.…”
Section: Introductionmentioning
confidence: 99%
“…The full texts of the 13 literatures were screened to examine their eligibilities on the basis of the inclusion and exclusion criteria. Among these, four studies were excluded [two reported control-only studies (Li and Su, 2013;Liu et al, 2014) and two did not analyze rs1625579 (Egawa et al, 2013;Ohi et al, 2013)]. Among the nine references included, one study included two independent case-control samples from a Chinese population .…”
Section: Literature Search and Eligible Studiesmentioning
confidence: 99%